2020
DOI: 10.4081/ripppo.2020.461
|View full text |Cite
|
Sign up to set email alerts
|

DBT-informed treatment in a partial hospital and intensive outpatient program: the role of step-down care

Abstract: Few studies to date have examined Partial Hospital (PH) and Intensive Outpatient (IOP) programs that utilize a Dialectical Behavior Therapy (DBT)-informed model. Preliminary findings suggest that DBT-informed PH programs are effective in reducing clinical symptoms; however, less is known about IOP programs as well as step-down care models. The present study utilized clinically relevant outcome indices and included a heterogeneous clinical sample. Specifically, the present study assessed pre-post data to examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 30 publications
1
1
0
Order By: Relevance
“…The present study findings replicate previous findings from Lothes et al, (2014;2016) that show symptom reduction from intake to discharge with unique clinical measures of depression (BDI & CUDOS) and anxiety (BAI & CUXOS) among a DBT-PH program. These results are like those found in prior literature of DBT being used in IOP programs that have demonstrated decreased depression and anxiety symptoms (Mochrie et al, 2020;Ritschel et al, 2012). However, this study extended prior research by examining outcomes that included hopelessness, self-reported overall suffering, which both showed significant decreases in all conditions.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The present study findings replicate previous findings from Lothes et al, (2014;2016) that show symptom reduction from intake to discharge with unique clinical measures of depression (BDI & CUDOS) and anxiety (BAI & CUXOS) among a DBT-PH program. These results are like those found in prior literature of DBT being used in IOP programs that have demonstrated decreased depression and anxiety symptoms (Mochrie et al, 2020;Ritschel et al, 2012). However, this study extended prior research by examining outcomes that included hopelessness, self-reported overall suffering, which both showed significant decreases in all conditions.…”
Section: Discussionsupporting
confidence: 84%
“…While in the PH program patients also had access to a medication prescriber weekly to discuss medication management and make any necessary medication changes. For a more detailed description of the DBT-PH program (Mochrie et al, 2019 andMochrie et al, 2020).…”
Section: Ph Program Descriptionmentioning
confidence: 99%